Analysis Of Agricultural Policy: Effectiveness Of Crop Insurance As A Safety Net For Representative Peanut Farms In The U.S. - Luke-Morgan, Audrey Susan (My University, 2018)
Agriculture touches everyone’s life. Agriculture, however, is not an industry without risks. Risks prevail for both farm families and consumers. The federal government intervenes through agricultural policy to alleviate these risks. Policymakers typically focus on providing agricultural assistance to minimize price, market or production risk for agricultural producers. A variety of programs devised by Congress and operated by the U.S. Department of Agriculture (USDA) support farm income and help farmers and ranchers manage production or price risks. The foundation of agricultural programs is government intervention intended to provide a farm safety net to agricultural producers. These programs aid in managing the food supply while stabilizing agricultural infrastructure. The 2014 Farm Act represents a shift in the direction of agricultural policy toward risk management policies, which offer a variety of programs for producers. Through multiple coverage options, these programs aim to raise producers’ revenues, on average, and reduce volatility. Specifically, federal crop insurance has expanded over the past two decades and is considered the most extensive component of the safety net provided by the current farm bill given the availability of policies for a considerable portion of U.S. agriculture. With federal crop insurance policies, producers pay a portion of the premium with the remainder subsidized by the federal government. The relative importance of federal crop insurance for a specific commodity or geographic region may be debatable. This study investigates the effectiveness of crop insurance as a safety net for U.S. peanut producers using case study analysis of representative peanut farms. Specifically, the financial stability of these farms is considered to test for correlations between crop insurance utilization and potential crop insurance indemnity payments. Crop insurance selection for a peanut enterprise is multi-faceted. Decisions must be made on policy type for a range of coverage levels and pricing options. This study considered a portion of those options. The level of effectiveness varied within each of the variables. In general, the yield protection model generated a greater level of effectiveness than the revenue protection or catastrophic policies but was effective on less than one-third of the total observations. A higher coverage level resulted in higher levels of effectiveness, but even at the maximum level tested, 75 percent coverage, less than three out of five of the observations were deemed effective. Differences in effectiveness were seen across regions and cultivars, with the maximum effectiveness for any of these only at one-third of the observations. When considering the effectiveness by farm size, farms with peanut acreage in the 750 to 999 range showed 60 percent positive observations. Finally, when looking at individual farms, crop insurance was effective for all crop insurance options analyzed for five percent of the farms. Ten percent of the farms had no positive observations regardless of coverage type or level. These results challenge the effectiveness of crop insurance as a safety net for peanut producers.
I: INTRODUCTION 1 | U.S. Agricultural Production and Agricultural Policy: Current Situation 2 | Purpose of Policy Analysis: Planning for 2018 Farm Bill 3 | Problem Statement 4 | Project Selection 5 | Significance of the Study: Effectiveness as a Policy Analysis Criterion 5 | Summary 6 | II: REVIEW OF LITERATURE 7 | Problem Statement and Overview 7 | Importance of Agriculture 8 | Historical Beginnings of U.S. Farm Programs 10 | Characteristics of U.S. Agricultural Production: Current Situation 12 | Evolution of Peanut Policy 14 | Federal Crop Insurance from Past to Present 16 | Participation in Federal Crop Insurance Programs 19 | Overview of Farm Economic and Financial Factors 21 | Concerns Surrounding Federal Crop Insurance Use 24 | Federal Crop Insurance: An Agricultural Example of Public Administration 24 | Summary 26 | III: METHODOLOGY 28 | Overview 28 | Research Objectives 29 | Research Questions 29 | Hypotheses 29 | Study Approach 30 | Data Source 31 | Data Estimation Model 32 | Multiple Peril Crop Insurance 32 | Cost to Producer 33 | Loss Examples 34 | Representative Peanut Farm Determined Data 34 | Study Variables 35 | Analytic Procedures 40 | Summary 41 | IV: RESULTS 42 | Crop Insurance in Peanuts at the National Level 42 | Representative Farm Characteristics 45 | Representative Farm Model 50 | Testing Hypothesis1: Relationship between CIU and FS 54 | Effectiveness of Crop Insurance Summary Analysis 55 | Summary 63 | V: CONCLUSION 65 | Study Overview 65 | Limitations of the Study 66 | Study Implications 67 | Recommendations for Future Research 68 | Reference List 70 | APPENDIX A: Institutional Review Board (IRB) Protocol Exemption Report 74 |
Keywords: Dissertations, Academic--United States; Public administration; Agriculture and state; crop insurance; Social Safety Net Programs; Peanut industry--Government policy; Farmers--Economic conditions